Effect of ZrSiO4 Concentration on the Microstructure and Corrosion Resistance of MAO Coatings Formed on AZ91 Magnesium Alloy - Li, Tianlu; Chen, Guorui; Xiang, Mingzhe; Zhao, Yun; Chen, Minfang (Frontiers in Materials, 2022)
As a metallic material with lightweight and high specific strength, magnesium alloy has excellent application prospects. However, the rapid corrosion rate and localized corrosion behavior of magnesium alloys limit the practical application in automobile industry. In this study, to improve the corrosion resistance of AZ91 alloy, the film of different concentrations zirconium-containing (AZR0, AZR5, AZR10, AZR15) was prepared on the surface of AZ91 alloy by micro-arc oxidation technology in Na2SiO3-Na3PO4 system. Furthermore, the influence of electrolyte composition on the corrosion resistance of MAO film was systematically investigated. The experimental results revealed that the ZrSiO4 particles added in the electrolyte could enter into the MAO film and ZrSiO4 particles were also decomposed into ZrO2 and Mg2Zr5O11 in the process of micro-arc oxidation. More importantly, the formation of micro-cracks and other defects in the film could be reduced after this process. The addition of 15 g·L-1 ZrSiO4 in the electrolyte was contributed to the best comprehensive properties of MAO-processed AZ91 specimens, including improved Vickers hardness of 167.16 Hv, Young's modulus of 652 MPa, and enhanced corrosion resistance (RP = 9.82×105 Ω·cm2). This approach could provide the approach for developing Mg-based materials with high anticorrosion in industrial fields.